Experimental optimization for synthesis of cerium-doped titanium dioxide nanoparticles by modified sol-gel process - Mousab Salaheldeen Mirghani (MethodsX)
A systematic experimental optimization procedure was developed for the synthesis of cerium-doped titanium dioxide nanoparticles (CeTNPs) based on modified sol-gel process. The nanocomposite was prepared using titanium tetraisopropoxide (TTIP) as a catalyst precursor, while utilizing the non-ionic surfactant Triton X-114 in cyclohexane as a stabilizing agent. The synthesis process was optimized by identifying the main experimental factors that affect the properties of the nanoparticles, primarily the structural phase and particle size. The synthesized samples were characterized by X-ray diffraction (XRD) for phase and size, field emission scanning electron microscope (FE-SEM) for morphology, particle size analyzer (PSA) for size distribution, and Brunaur, Emmett, and Teller (BET) for surface area and pores characteristics. The photocatalytic activity of the optimized sample was tested for the removal of methyl orange (MO) and lead (II) from aqueous solutions, and the results indicate superior performance as the catalyst uptakes were 14.8 mg/l and 11.4 mg/l for methyl orange and lead (II), respectively.The main highlights of the proposed procedure are as follows: • Identification of the key variables impacting the structural and morphological properties. • Establishing the levels of each factor based on experimental findings. • Generation of all possible combinations of factors based on ANOVA, then characterization of the synthesized material from every possible combination.